Hybrid Algorithms to Solve Linear Systems for Finite-Element Modeling of Filtration Processes - Baranov, A. Yu; Bilous, M. V.; Sergienko, I. V.; Khimich, A. N. (Cybernetics and systems analysis, 2015)
We consider a new parallel algorithm to solve systems of linear algebraic equations with band symmetric positive definite matrix, which combines computations on multi-core processors and graphics processing units. We present the results of simulation of spatial filtration of groundwater for Chernihiv region with Nadra-3D finite-element solver.